The right to privacy : origins and influence of a nineteenth-century idea - Richardson, Megan (Cambridge intellectual property and information law, 2017)
"A sense of Victorian probity and piety was a signal feature of the case of Prince Albert v Strange, coming twelve years after Queen Victoria's ascension to the throne in 1837, and a year after a series of troubling revolutions in Europe (see Evans, 2